Study on the growth, reproduction and morphology of raft and drifting S. horneri in Gouqi Island - Huijie Wang; Qifan Yang; Weidong Zhu; Hang Miao; Fengyu Liu; Yuanxin Bi; Yuanxin Bi (Frontiers in Marine Science)
Drifting Sargassum horneri (S. horneri) may form "golden tide", in order to analyze the source and occurrence mechanism of drifting S. horneri in the sea area of Gouqi Island, Zhejiang, and to determine whether drifting S. horneri possesses sexual reproductive capability, from September 2022 to May 2023, during the life cycle of the raft S. horneri, the growth, reproduction and morphological differences between raft S. horneri and raft whole、cutting raft S. horneri after simulated drifting life (simulated drifting S. horneri) were studied, and reproduction of natural drifting S. horneri in the sea area of Gouqi Island was observed. The results showed that: (1) Both raft and simulated drifting S. horneri had the ability to reproduce sexually, but the number of receptacles of simulated drifting S. horneri were significantly smaller than that of raft S. horneri in the same month (P<0.05); If fixed S. horneri float long distances after being released from attachment base, growth environment such as temperature and light intensity will change greatly, distribution ratio of growth and reproduction is affected, it may not have the ability to reproduce sexually, and even phenomenon of reproductive alienation will occur. (2) Except for December to February, when the temperature and light intensity were lower, the relative growth rate (RGR) of the simulated drifting S. horneri was significantly higher than that of the raft S. horneri in the same month (P<0.05). This may be attributed to higher sea surface temperatures, greater light intensity, richer nutrient availability, and a resource allocation mechanism favoring growth. (3) The longest primary branch length could be used as an important morphological parameter to distinguish raft and simulated drifting S. horneri. (4) The number of benthic S. horneri on Gouqi Island is decreasing year by year, and a large number of S. horneri are attached to the raft culture facilities, due to their fast growth, long drifting period and strong diffusion ability after drifting life, most of drifting S. horneri in the sea area near Gouqi Island may be derived from raft S. horneri.The above results can provide a scientific basis for the research on the source of drifting S. horneri, ecological restoration and prevention of "golden tide" in the waters near Gouqi Island.